The genetic basis of drought resistance in tomato - Rosa, Bruno Luan (2022)
The development of crop varieties capable of maintaining satisfactory yields under stressful conditions such as drought is an important step towards ensuring adequate food production in the future. In this context, natural genetic variation in tomato can be allied with modern techniques such as the production of introgression lines, as well as mutant and transgenic organisms in the search for varieties more resistant to water deficit. Here, we show that S. pennellii introgression lines IL2-5, IL4-3, and IL2-5/4-3 exhibit increased leaf succulence, as well as significant changes in leaf thickness and stomatal density. Together, these leaf traits contributed to the maintenance of leaf water status, which improved photosynthetic performance and plant resilience when subjected to drought conditions. In this work, we also demonstrated the physiological and hydraulic changes caused by an allelic variant of the OBSCURAVENOSA (OBV) gene. In addition to controlling the development of vascular bundle sheath extensions (BSE), this gene also resulted in significant changes in leaf insertion angle, leaf margin serration, venation density, and fruit shape. We found that BSE development is strongly linked functionally to the auxin signaling network involving AUXIN RESPONSE FACTOR 4 (ARF4). Lastly, we show that loss of function of ARF4 alters leaf structure, resulting in a phenotype with severe leaf curling and low stomatal conductance. Loss of ARF4 function increased water and abscisic acid content in leaves, resulting in significant improvements in tomato plant resistance to salt and osmotic stress. Our data provide evidence that anatomical and morphological changes in leaves, whether from natural genetic variation or genetically modified organisms, can help to better understand the process of resistance to abiotic stress, such as drought and salinity. Thus, we suggest that mapping and identifying the genes responsible for the leaf traits demonstrated here may help in the creation of future varieties that are more resistant to water deficit. Keywords: Solanum pennellii. Introgression lines. Auxin. CRISPR-Cas9. Bundle sheath extensions. Drought stress.